From newspeak to cyberspeak : a history of Soviet cybernetics - Gerovitch, Slava (MIT Press, 2002)
In this book, Slava Gerovitch argues that Soviet cybernetics was not just an intellectual trend but a social movement for radical reform in science and society as a whole. Followers of cybernetics viewed computer simulation as a universal method of problem solving and the language of cybernetics as a language of objectivity and truth. With this new objectivity, they challenged the existing order of things in economics and politics as well as in science. The history of Soviet cybernetics followed a curious arc. In the 1950s it was labeled a reactionary pseudoscience and a weapon of imperialist ideology. With the arrival of Khrushchev's political "thaw," however, it was seen as an innocent victim of political oppression, and it evolved into a movement for radical reform of the Stalinist system of science. In the early 1960s it was hailed as "science in the service of communism," but by the end of the decade it had turned into a shallow fashionable trend. Using extensive new archival materials, Gerovitch argues that these fluctuating attitudes reflected profound changes in scientific language and research methodology across disciplines, in power relations within the scientific community, and in the political role of scientists and engineers in Soviet society. His detailed analysis of scientific discourse shows how the Newspeak of the late Stalinist period and the Cyberspeak that challenged it eventually blended into "CyberNewspeak."